2014
DOI: 10.1021/om500266p
|View full text |Cite
|
Sign up to set email alerts
|

Catalyst Activation with Cp*RhIII/IrIII–1,2,3-Triazole-Based Organochalcogen Ligand Complexes: Transfer Hydrogenation via Loss of Cp* andN-MethylmorpholineN-Oxide Based vs Oppenauer-Type Oxidation

Abstract: The reactions of 1-benzyl-4-((phenylthio/phenylseleno)methyl)-1H-1,2,3-triazole (L1/L2) and 4-phenyl-1-((phenylthio/phenylseleno)methyl)-1H-1,2,3-triazole (L3/L4), synthesized using the click reaction, with [(η5-Cp*)RhCl(μ-Cl)]2 and [(η5-Cp*)IrCl(μ-Cl)]2 at room temperature followed by treatment with NH4PF6 result in complexes of the type [[(η5-Cp*)M(L)Cl] (1–8). Their HR-MS and 1H, 13C{1H}, and 77Se{1H} NMR spectra have been found characteristic. The single-crystal structures of 2, 3, and 6 have been establis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
139
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(140 citation statements)
references
References 132 publications
1
139
0
Order By: Relevance
“…418 The complexes 127 having the N(2) atom of 1,2,3-triazole coordinated to the rhodium center have shown better activity in the TH of ketones than 126 in which N(3) is involved in ligation. Moreover, the reactivity with respect to the ligands is in the order Se > S. 479 The mechanistic studies indicated that the Rh species that had lost the Cp* ligand was an intermediate in the catalytic cycle. The iridium analogues of complexes 123, 124, 126, and 127 were also synthesized and exhibited even better catalytic performances in TH reactions than these rhodium counterparts (Scheme 46).…”
Section: Osmium-based Catalystsmentioning
confidence: 99%
“…418 The complexes 127 having the N(2) atom of 1,2,3-triazole coordinated to the rhodium center have shown better activity in the TH of ketones than 126 in which N(3) is involved in ligation. Moreover, the reactivity with respect to the ligands is in the order Se > S. 479 The mechanistic studies indicated that the Rh species that had lost the Cp* ligand was an intermediate in the catalytic cycle. The iridium analogues of complexes 123, 124, 126, and 127 were also synthesized and exhibited even better catalytic performances in TH reactions than these rhodium counterparts (Scheme 46).…”
Section: Osmium-based Catalystsmentioning
confidence: 99%
“…Thus argon or nitrogen atmosphere 22,23 is required during catalysis to protect catalyst from deactivation. In view of moisture and air sensitivity of these complexes, a number of Pd(II) species bearing chalcogen (S, Se or Te) ligands, [26][27][28] have been explored as possible alternatives to catalyse various chemical transformations 29,30 including C-C coupling reactions. [31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48] The catalytic activity of some of these complexes (thermally stable and resistant to aerial oxidation) not only rivals but vastly outperforms that of the corresponding phosphorus analogues.…”
Section: Introductionmentioning
confidence: 99%
“…These ligands are 1,2,3-triazole based and in the recent past, applications of such organochalcogen ligands in designing catalysts for transfer hydrogenation and oxidation have been reported by our group. 29,30 The synthesis of palladium complexes of a (P, C, S) pincer ligands having 1,2,3-triazole skeleton and their applications in Heck coupling are known. 49 The presence of 1,2,3-triazole unit in a ligand offers an interesting alternative to the traditional phenyl based framework and has been found to render interesting variation in catalytic activities of metal complexes of such ligands, due to potential of this unit to act as a N donor through two types of nitrogen atoms: viz., N(2) and N(3).…”
Section: Introductionmentioning
confidence: 99%
“…This method has been widely used for synthesizing several ligands comprising 1,4-disubstituted 1,2,3-triazolyl groups [9][10][11][12][13][14]. The metal complexes of these ligands have drawn attention because of their catalytic activities in many organic transformations [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%